2017
DOI: 10.1103/physrevlett.118.127401
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic Spectroscopy with Submolecular Resolution from STM-Induced Electroluminescence

Abstract: A scanning tunneling microscope is used to generate the electroluminescence of phthalocyanine molecules deposited on NaCl/Ag(111). Photon spectra reveal an intense emission line at ≈1.9  eV that corresponds to the fluorescence of the molecules, and a series of weaker redshifted lines. Based on a comparison with Raman spectra acquired on macroscopic molecular crystals, these spectroscopic features can be associated with the vibrational modes of the molecules and provide a detailed chemical fingerprint of the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
128
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 27 publications
11
128
0
2
Order By: Relevance
“…The emission is 30 times more intense at positive voltage where low energy vibronic features are also observable. Similar light emission features (18,20,21,(23)(24)(25) were assigned to an excitation of a decoupled molecule by an energy transfer from an inelastic tunneling electron, possibly mediated by localized plasmons (see sketch Fig.1(E)).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…The emission is 30 times more intense at positive voltage where low energy vibronic features are also observable. Similar light emission features (18,20,21,(23)(24)(25) were assigned to an excitation of a decoupled molecule by an energy transfer from an inelastic tunneling electron, possibly mediated by localized plasmons (see sketch Fig.1(E)).…”
mentioning
confidence: 70%
“…The electronic and electroluminescent (EL) properties of single ZnPc molecules separated from a Au(111) surface by three layers of NaCl are shown in Fig.1(A). The dI/dV spectrum acquired on a single molecule ( Fig.1(B)) revealed an electronic gap of 3.2 eV between the high- characteristic of the fluorescence of a single ZnPc molecule in its neutral form (20,22,23). The emission is 30 times more intense at positive voltage where low energy vibronic features are also observable.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The rotating molecule shown in the bottom row of Fig.2 exhibits the previously described STM contrast of 16 lobes. 25 26 5 The AFM taken at 25 mV confirms that there are two distinguishable angular positions, since the angular switching slows down enough to hold each position at timescale of minutes.…”
mentioning
confidence: 84%
“…21 However, it has been reported that using Ag(111) as a metallic substrate leads to the same 1.9 eV exciton radiative decay detectable at negative biases. 25 Therefore, we performed experiment on the ZnPc/NaCl/Ag(111) system and obtain Comparing the photon maps obtained on the Au(111) at positive biases and Ag(111) at negative biases with metal and CO-tips, we see striking differences corresponding mainly to the distinct spatial modulation of the charge carrier transport. On both substrates the individual normalized spectra show an identical lineshape, which implies that we observe the radiative decay of the same final S1 excited state.…”
mentioning
confidence: 99%